ANALISIS KESELARASAN PENGGUNAAN LAHAN DENGAN POLA RUANG RTRW DI KABUPATEN INDRAMAYU PROVINSI JAWA BARAT - Sodikin Sodikin; Mujio Mujio; Santun R.P. Sitorus (Program Pascasarjana Universitas Riau, 2022)
This study aims to analyze the alignment of existing land use in the Indramayu Regency in 2021 with the spatial pattern of the RTRW of Indramayu Regency in 2011-2031. The data used in this study include Google Earth images in 2021, maps of the administrative boundaries of the Indramayu Regency, and maps of Indramayu Regency spatial patterns in 2011-2031. The analytical technique used in this research is to use the overlay technique, which is to overlay the existing land use map with a spatial pattern map, then a query is made based on the logical matrix of the alignment of land-use types with spatial patterns which produces a map of the alignment of land use with spatial patterns in Indramayu Regency. The results showed that there were 15 types of land use in Indramayu Regency. The largest land use in Indramayu Regency is rice fields with an area of 131,631 (62.9%) of the total land area of the Indramayu Regency). The majority of land in the Indramayu Regency is still in harmony with the planned spatial pattern by 70.31%, transitional land by 6.70%, and not aligned by 22.98%. Land that is not in harmony is widely found in protected forests and paddy fields. Most of the protected forest area in Ithe Indramayu Regency has been turned into a pond area, and the rice field area has become residential land, both village settlements, and urban settlements.